PENGGUNAAN PENDEKATAN ANDRAGOGI DALAM PROSES PEMBELAJARAN NONFORMAL - Putu Yulia Angga Dewi; Kadek Hengki Primayana (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2021)
Non-formal education is an educational activity carried out in an organized, planned manner outside the school system, which is intended by individuals or groups in society to improve their quality of life. In education, the existence of methods is also very important. Various innovations related to this method emerged as a result of the times. Of course, this latest method must be compatible with all aspects related to the learning system. In general, Andragogy is often used in the learning process at the upper secondary education level. In the learning process, the application of concepts and principles contained in the andragogy learning theory, actually does not have to be completely based on the form, unit level/level of education, but the most that must be considered is based on the readiness